Prospective Analysis of Patents of The Use of Ziziphus joazeiro (Juá) - Pinto, Eladio Cesar (2020)
The Ziziphus joazeiro is native to Brazil, with emphasis on the North and Northeast regions, although it can be found in several parts of the world with dry and arid climates. According to the literature, the plant is used in folk medicine, as in infusions for anti-inflammatory action and in hair tonics for scalp treatment. This article aims to analyze articles in journals and publications in national and international patents, in order to guide the development of new formulations from the field. For this, searches were carried out in the databases of Capes, Science Direct and Google Scholar, as well as in Orbit to search for patents. It is worth mentioning the still small number of patents (14 in the world, six of which are Brazilian) on the subject, when compared with the number of articles (86); Finally, it was verified that families of international patents, specifically American ones, have protection in Brazil, limiting their production and commercialization where the plant is native.